Correlative microscopy analyses of thin-film solar cells at multiple scales. (July 2017) - Abou-Ras, Daniel
Abstract: In the present work, a brief overview is given on how to apply transmission (TEM) as well as scanning electron microscopy (SEM) and their related techniques (electron diffraction, energy-dispersive X-ray spectrometry, electron energy-loss spectroscopy, electron holography; electron backscatter diffraction, electron-beam-induced current, cathodoluminescence) for the analysis of interfaces between individual layers or extended structural defects in a thin-film stack. All examples given in the present work were recorded on Cu(In, Ga)Se2 thin film solar cells, however, the shown experimental approaches may be used on any similar thin-film semiconductor device. A particular aspect is the application of various techniques on the same identical specimen area, in order to enhance the insight into structural, compositional, and electrical properties. For (aberration-corrected) TEM, the spatial resolutions of such measurements can be as low as on the subnanometer scale. However, when dealing with semiconductor devices, it is often necessary to characterize electrical and optoelectronic properties at larger scales, of few 10 nm up to even mm, for which SEM is more appropriate. At the same time, these larger scales provide also enhanced statistics of the analysis. In the present review, it is also outlined how to apply SEM techniques in combination with scanning-probe and optical microscopy, on the same identical positions. Altogether, a multiscale toolbox is provided for the thorough analysis of structure-property relationships in thin-film solar cells using correlative microscopy approaches.